Spatial Price Differentiation and Regional Market Power. The Case of Food-Retailing in Austria - Dieter Pennerstorfer; Franz Sinabell (Austrian Institute of Economic Research (WIFO), 2013)
A small number of firms have a large market share in the Austrian food retailing market. Market concentration has been growing over the last years which has raised concerns about market power. Previous studies on price setting behaviour in the food retailing market were at the national level and regional price setting has not yet been analysed. We use a panel data set of over 2,000 households with monthly food purchasing data and the number of outlets of the nine biggest food retailers in 120 districts to explore regional price setting behaviour. The analysis shows that only a small number of retailers seem to regionally differentiate prices extensively. It cannot be confirmed that spatial price differentiation is a way to exert market power in the Austrian food retailing market.
Keywords: 330; Market power; Food retailing; Spatial price differentiation; Austria; Marktmacht; Preisdifferenzierung; Regionaler Preisindex; Lebensmitteleinzelhandel; Österreich